Multiperiod Logit on Survival Analysis of Financial Distress in Manufacturing Company - Wilda Yulia Rusyida; Anas Yoga Nugroho (J STATISTIKA: Jurnal Imiah Teori dan Aplikasi Statistika, 2023)
The company is required to be able to maintain its survival so that the company's goals can be achieved properly. Financial distress is one of the factors that causes the company to be unable to maintain its viability so that the company's goals are not achieved. The factors that cause the company to be in a state of distress are internal and external factors. This is descriptive quantitative research which used 16 financial ratios, IHSG and BI rate. This research method is a quantitative method using time series data with a multiperiod logit model. Determination of the sample using purposive sampling so that there are 79 samples used in this study. Based on the results of the description of the Kaplan Meier curve, log rank test, multiperiod logit model with variable selection, it means that companies survive and financial distress have prominent differences in profitability ratios and market measure ratios. Meanwhile, based on the results of the partial test 4 out of 5 financial ratios, the results of the selection of variables have a significant effect on financial distress. The five best companies to invest in with a minimum hazard opportunity value are companies with issuer codes SKBM, IGAR, PBRX, PSDN and UNIC.